Influence Individual Nutrition Counseling with Booklet Media on Hb Levels of Pregnant Women in the Wedi Regency Health Center Area Klaten - Mariyana, Anna; Sandi Ulya, Pramitha; Prastyoningsih, Aris (Journal of Advanced Nursing and Health Sciences, 2024)
Background​ Incident maternal anemia in Indonesia is a consequence deficiency iron Still figure 48.9% (Riskesdas, 2018). Anemia is circumstances No sufficient erythrocytes For deliver need oxygen marked network​ with low Hb concentration <11gr/dl (Wibowo et al., 2021). Causative factor incident that's one of them is pattern consumption food Mother pregnant who is not various. Subjects and methods : Type of research used is quasi experiment with design Pre-post Control Design and data is collected with use questionnaire with amount sample as many as 60 mothers pregnant . Taking sample in study This will use purposive sampling. Data analysis used the Paired T- Test for paired and Unpaired T-Test for those who don't pair. Results : There is influence significant in a way statistics counseling nutrition individual with booklet media enhancement Hb levels of pregnant women with p value < 0.05 (0.000), in group intervention, the average increase in Hb was more than 0.50 gr/dl big from group control 0.20 gr/dl.